Carbon nanotube/nickel foam-mannitol phase change composite material for medium-temperature solar energy storage and conversion. (1st November 2022) - Wang, Min; Wu, Zihua; Liu, Anbang; Wang, Yuanyuan; Xie, Huaqing
Abstract: Researches on medium-temperature thermal storage technology based on phase change material (PCM) have gradually grown to be the backbone of the development of concentrated solar power system. However, conventional PCM represented by mannitol (C6 H14 O6, abbreviated as MA) is difficult to achieve the desired effect in practical applications, because its own disadvantages such as severe undercooling, low thermal conductivity, poor solar energy absorption and easy to leakage. To overcome above problems, this work uses a skeleton composed of carbon nanotubes (CNTs) and nickel foam (NF) on the basis of MA to prepare a new type of composite PCM: CNT/NF-MA. The CNT/NF skeleton is prepared by growing CNTs on the NF framework through using chemical vapor deposition method to achieve full-spectrum solar absorption. In addition, the CNT/NF skeleton also provides a large number of heterogeneous nucleation sites, lowers the nucleation energy barrier for the formation of mannitol crystals during solidification. Thus, it facilitates heat transfer along the 3D network and restricted the liquidity of molten MA. Compared to the pure MA, the CNT/NF-MA reduces the undercooling from 53.6 °C to 43.2 °C and the thermal conductivity increases by 148.8 %. The DSC results shown that the CNT/NF-MA has a superior heat storage capacity and excellent photothermal conversion ability. Its potential heat storage can reach to 314.4 J/g, the surface temperature can rise from ambient temperature to 234.7 °C within 1000 s under 700 mW/cm 2 sunlight and the photothermal conversion efficiency is as high as 86 % at the same time. In the future, the CNT/NF-MA composite PCM is expected to further improve efficiency in medium-temperature solar energy utilization. Highlights: A new tape of composite PCM overcoming the problems of the based PCM has been designed and fabricated. The composite PCM consists of NF as the framework to achieve full spectrum solar absorption and mannitol as an organic PCM. CNTs are grown on the NF framework by CVD method to provide superior nucleation and heat transfer performance of PCMs. CNT/NF-PCM reduces the subcooling of mannitol significantly and increases the thermal conductivity by 148.8%. Surface temperature of CNT/NF-PCM rises to 234.7 °C within 1000s under sunlight and the photothermal conversion efficiency reaches 86%.